Public opinion and interest groups' concerns for organizational survival. Issue 2 (31st May 2019) - Hanegraaff, Marcel; Poletti, Arlo
Abstract: A growing number of studies focus on the two-way channels connecting public opinion and interest groups, highlighting how public support affects interest groups' mobilization, strategies, and influence, while also showing how interest groups manage to shape public opinion. We contribute to this debate, assuming that interest groups are fundamentally survival-maximizing organizations. First, we investigate whether public opinion bears on advocacy groups' assessment of their own survival prospects. Second, we assess whether public opinion-driven mortality anxiety affects advocacy groups' choices regarding different lobbying strategies. Empirically, we rely on data from the Comparative Interest Group Survey, including over 2500 interest group respondents across six European Union (EU) countries as well as groups working at the EU level. Our analysis shows that (1) public opinion crucially influences how advocacy groups estimate their chances of survival, particularly for citizen groups and (2) public opinion-related survival concerns stimulate greater relative use of outside lobbying by citizen groups.